2022
DOI: 10.1002/adma.202202164
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Phase Exfoliation of Nonlayered Non‐Van‐Der‐Waals Crystals into Nanoplatelets

Abstract: For nearly 15 years, researchers have been using liquid‐phase exfoliation (LPE) to produce 2D nanosheets from layered crystals. This has yielded multiple 2D materials in a solution‐processable form whose utility has been demonstrated in multiple applications. It was believed that the exfoliation of such materials is enabled by the very large bonding anisotropy of layered materials where the strength of intralayer chemical bonds is very much larger than that of interlayer van der Waals bonds. However, over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 201 publications
(627 reference statements)
1
58
0
Order By: Relevance
“…[38] However, recently we and others have observed that nonlayered bulk materials such as Fe 2 O 3 , [39] FeS 2 , [40] FeF3, [41] α-Ge, [42] Si, [43] etc., can also be exfoliated into nanoplatelets by LPE. [39][40][41][42][44][45][46] However, in such a system, the only process taking place is fragmentation, that is, rupturing of bonds by the sonication-induced microjets. [46] It is still unknown why this process results in the formation of 2D platelets rather than quasi-spherical nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[38] However, recently we and others have observed that nonlayered bulk materials such as Fe 2 O 3 , [39] FeS 2 , [40] FeF3, [41] α-Ge, [42] Si, [43] etc., can also be exfoliated into nanoplatelets by LPE. [39][40][41][42][44][45][46] However, in such a system, the only process taking place is fragmentation, that is, rupturing of bonds by the sonication-induced microjets. [46] It is still unknown why this process results in the formation of 2D platelets rather than quasi-spherical nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Among all these techniques, LPE is one of the most used methods to produce 2D nanosheets on a large scale. The search for 2D materials has gone beyond these layered materials, exploring the direct exfoliation of nonlayered 3D crystals using LPE [ 8 ]. In 2017, Guan et al [ 9 ] were able to exfoliate monoclinic tungsten trioxide crystals by LPE, opening the door to use other nonlayered strongly bonded crystals as starting materials to prepare 2D nanosheets following this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of those materials is the additional effort in the material synthesis, which increases the cost of the manufactured anode and the scaling up for industrial use. In this way, recent investigations focus on alternatives to obtain materials using cost-effective and large-scalable methods [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] Compared with the clean‐room fabrication methods like chemical vapor deposition (CVD), pulsed laser deposition (PLD), molecular beam epitaxial growth (MBE), etc., the wet‐chemical synthesis approaches provide an alternative route for low‐cost and large‐scale fabrication of 2D materials nanoflakes without the requirements of expensive instrumentation, stringent vacuum environments, and complex operations. [ 14 , 15 , 16 , 17 ] Due to weak inter‐layer bonds (van der Waals bonds) of the 2D materials, they can be easily separated into liquid‐dispersed mono‐ or few‐layered 2D materials nanoflakes by liquid exfoliation and used to construct 2D and 3D macrostructures and nanofilms by a range of subsequent processing methods such as layer‐by‐layer assembly (LBL), Langmuir–Blodgett assembly (LB), spin coating, inkjet printing, spray coating, vacuum filtration, interfacial assembly, freeze‐drying, and so on. [ 18 ] Among these approaches, the interfacial assembly received enormous attention because it allows large‐scale production of densely packed nanometer‐thick films with good reproducibility and improved electrical conductivity, higher sensing factor, superior mechanical properties, and so on.…”
Section: Introductionmentioning
confidence: 99%